1993
DOI: 10.1523/jneurosci.13-06-02351.1993
|View full text |Cite
|
Sign up to set email alerts
|

Highly polysialylated neural cell adhesion molecule (NCAM-H) is expressed by newly generated granule cells in the dentate gyrus of the adult rat

Abstract: We have found in the adult rat that the persistent expression of a highly polysialylated neural cell adhesion molecule (NCAM-H) that is generally specific to developing tissues, remains restrictively in the cells of the deepest portion of the dentate granular layer. Since the granule cells are known to continue to be generated in this region during the adult period, we have tried to determine whether NCAM-H is expressed by newly generated granule cells. Immunoelectron microscopic observation revealed that abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
280
1
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(304 citation statements)
references
References 35 publications
21
280
1
2
Order By: Relevance
“…44,45 Immature type II progenitors cells divide and will later show properties of neurons, e.g., express doublecortin (DCX), poly-sialylated neural adhesion molecule (PSA-NCAM), or neuronal nuclei (NeuN). 7,45,47 Until recently, NSCs had only been observed in the SVZ and SGZ of the healthy mammalian brain. However, an intriguing study identified neural progenitor cells in the neocortical layer 1 of adult rats subjected to mild ischemia.…”
Section: The Developing Mammalian Brainmentioning
confidence: 99%
“…44,45 Immature type II progenitors cells divide and will later show properties of neurons, e.g., express doublecortin (DCX), poly-sialylated neural adhesion molecule (PSA-NCAM), or neuronal nuclei (NeuN). 7,45,47 Until recently, NSCs had only been observed in the SVZ and SGZ of the healthy mammalian brain. However, an intriguing study identified neural progenitor cells in the neocortical layer 1 of adult rats subjected to mild ischemia.…”
Section: The Developing Mammalian Brainmentioning
confidence: 99%
“…The de-adhesive properties of PSA-NCAMs have been suggested to counteract the stressinduced excess glutamatergic input (Hoffman et al, 1997;Rutishauser, 1998;Sandi, 2004) and/or the reduction in BDNF that follows chronic stress protocols (Smith et al, 1995). As polysialylation of NCAM is critical for neurogenesis (Seki and Arai, 1993;Franceschini et al, 2001) and for synaptic plasticity (Muller et al, 1996), increased PSA-NCAM expression levels were suggested to represent a compensatory response to the deleterious structural effects of stress (Sandi et al, 2001). …”
Section: Exposure To Stress During Juvenility Alters Emotional Responmentioning
confidence: 99%
“…In the adult mammalian hippocampus PSA-NCAM expression is mainly located in a subpopulation of granule cells located in the innermost region of the granular layer of the dentate gyrus (Seki andArai 1991). Many of these cells are recently generated neurones (Seki and Arai 1993), which could be migrating to upper rows of the granule cell layer or extending their projections.…”
Section: Migration and Maturation Of Newly Generated Neuronesmentioning
confidence: 99%